Occupational stress management in managerial employees: an analysis of level and source of work stress - Untarini, Nindria; Sayyida, Sayyida; Singh, Sanju Kumar (BISMA (Bisnis dan Manajemen), 2020)
The sources and effects of stress have been conceptualized from several theoretical and empirical perspectives. This study explores the sources and impacts of job stress in managerial levels in two different countries, namely developing and developed countries. Furthermore, how to deal with and manage job stress for managers are also described. This study reviews the level and source of work stress that researched in academic journals, books, proceedings, reports, and website. After reviewing the literature extensively, it is concluded that managers in each of the two groups of countries experience workplace stress with different work stress sources. Meanwhile, the impact of job stress at the managerial level in the two groups of countries is almost identical. Job stress affects job satisfaction, mental and physical health, high intention to quit the job, and high absenteeism rates. The strategy to ensure employee health and well-being is to provide a stress-free work environment by creating supportive organizational systems, stress auditing, counselling, education and training, and work balance initiatives. It is hoped that the results of this study can be made a role model in managing stress in the work environment, especially at the managerial level, based on the source and impact of work stress so that it can be used as a basis for designing strategies and policies to deal with stress in the workplace. Finally, this study provides guidelines for further research on this topic.